FUNDAMENTAL PROBLEMS OF COMPARATIVE ANTHROPOLOGY - Ременець, О. В. (Proceedings of the National Aviation University Series Philosophy Cultural, 2015)
This article analyzes the fundamental problems of comparative anthropology, in particular duality of human nature.